2011
DOI: 10.1027/0227-5910/a000054
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk and Its Relationship to Change in Marital Status

Abstract: Marital status change represents a risk factor for suicidal behavior. The first year after the change is critical for elevated suicidal risk, in particular for older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
1
19
2
Order By: Relevance
“…Being married and being in‐training status were associated with lower suicide risk. Marriage has been documented as a protective factor against suicide risk in the civilian research literature (Roskar et al., ). Those in training likely have lower risk due to the selection criteria for training as well as being on active duty with greater opportunity for suicide‐risk soldiers being noticed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Being married and being in‐training status were associated with lower suicide risk. Marriage has been documented as a protective factor against suicide risk in the civilian research literature (Roskar et al., ). Those in training likely have lower risk due to the selection criteria for training as well as being on active duty with greater opportunity for suicide‐risk soldiers being noticed.…”
Section: Discussionmentioning
confidence: 99%
“…Other more frequent events included the following: family conflicts (28% of all ARNG suicides), substance abuse (27%), past behavioral health problems (20%), and income and employment problems (22% and 18%, respectively). Interpersonal problems, financial difficulties, substance abuse and behavioral health conditions, and performance problems have been associated with suicide cases among active duty personnel (Millikan, Spiess, Mitchell, Fulcher et al., ; Millikan, Spiess, Mitchell, Watts et al., ) and civilian suicides (Roskar et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Turvey et al (Turvey et al, 2002) studied 1,617 subjects living in Iowa and found that financial losses were associated with higher rates of suicidal ideation. In regards to relationship losses, Roskar et al (Roskar et al, 2011) examined 1,614 suicide victims and 4,617 controls and found that suicide was associated with a change in marital status, especially in the first year right after the status change.…”
Section: Discussionmentioning
confidence: 99%
“…In population‐based samples from nine countries, divorced or separated individuals had higher rates of suicidal ideation and suicide attempts than currently married individuals (Weissman et al., ). Interestingly, authors of a study of suicide in Slovenia proposed that changes in marital status were more important than current marital status in predicting suicidal behavior (Roškar et al., ). The study found that individuals who had been divorced, widowed, or married in the preceding 5 years were at an increased risk of committing suicide relative to individuals who had not had a change in marital status and had stayed married or unmarried over the previous 5 years.…”
Section: Marriage and Suicidementioning
confidence: 99%